2014
DOI: 10.1074/jbc.m114.575613
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TRB3 Alters Dynamics of MLK3-JNK Signaling and Inhibits Cytokine-activated Pancreatic Beta Cell Death

Abstract: Background: MLK3 induces TRB3 to inhibit AKT and compromise beta cell survival. Results: AKT regulates novel phosphorylation, ubiquitination, and degradation of MLK3, explaining why TRB3 Ϫ/Ϫ islets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…In order to clarify the mechanism by which PRL modulates JNK, we assessed the role of AKT kinase in this context. The AKT pathway is an important antiapoptotic signal that inhibits the MAPK cascade involved in cytokine-induced JNK activation (Franke et al 1997, Humphrey et al 2014), and we have previously shown that PRL induces PI3K/AKT during pregnancy (Amaral et al 2004). We presently observed that PRL increases the phosphorylation of AKT and demonstrated that the inhibition of this AKT activation prevent PRL inhibitory effects and even increases cytokine-induced JNK activation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to clarify the mechanism by which PRL modulates JNK, we assessed the role of AKT kinase in this context. The AKT pathway is an important antiapoptotic signal that inhibits the MAPK cascade involved in cytokine-induced JNK activation (Franke et al 1997, Humphrey et al 2014), and we have previously shown that PRL induces PI3K/AKT during pregnancy (Amaral et al 2004). We presently observed that PRL increases the phosphorylation of AKT and demonstrated that the inhibition of this AKT activation prevent PRL inhibitory effects and even increases cytokine-induced JNK activation.…”
Section: Discussionmentioning
confidence: 96%
“…AKT is a modulator of JNK activation (Humphrey et al 2014). We next evaluated whether the observed decrease in cytokine-induced JNK phosphorylation, induced by PRL (Fig.…”
Section: Prl-decreased Jnk Activation Is Dependent Of Aktmentioning
confidence: 99%
“…We detected that MLK3 was expressed at a higher level in psoriatic tissues. MLK3 plays important roles not only in regulation of inflammatory mediator secretion by controlling the transcriptional activity of Janus kinase and NF‐κB, but also in the mitogen regulation of B‐Raf and extracellular signal‐related kinase . Silencing MLK3 in NHEKs significantly attenuated the cell proliferation and chemokine secretion promotion of the miR‐145‐5p inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, Humphrey et al have demonstrated that TRB3 is required for optimal MLK3-JNK activation in pancreatic beta cells. 20 Adding SB203580 was demonstrated as enhancing the expression of TRB3 in response to 4-hydroxy-trans-2-nonenal (4-HNE) in PC12 cells. 21 Furthermore, Zhang et al indicated that TRB3 may be involved in diabetic nephropathy by regulating the collagen type IV through the ERK1e2 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%